Peningkatan Keaktifan dan Hasil Belajar pada Materi Bangun Datar menggunakan Papan Berpaku untuk Kelas IV - Gigih Prihantono; Muflikhul Khaq; Titi Anjarini (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This research aims to improve the activeness and learning outcomes of fourth grade students of SD Negeri Banyuurip in Mathematics by using nailed board media. The subjects in this study were the fourth grade students of SD Negeri Banyuurip, totaling 10 students. Data collection techniques used are interviews, tests, observations, field notes, and documentation. The results of this study indicate that the nailed board media can increase the activity and learning outcomes of class IV SD Negeri Banyuurip. This is evidenced by the data obtained through observation and tests. The observations that have been made have shown good results, this is evident from the increase in the percentage in the pre-cycle and each cycle. In the pre-cycle stage, the percentage was 65.5%, the first cycle rose to 74.5%, and the second cycle rose again to 86%. This can be interpreted, that through observation, fourth grade students have reached the success indicator of 80% and are categorized as good. In addition to the results of observations, the tests that have been carried out have also increased, from the pre-test percentage of 49% of students completing the KKM, in post-test 1 in cycle 1 it increased by a percentage of 50%. In post-test 2, cycle two increased with a percentage of 86%. Thus, the achievement of the competencies produced by the percentage of 86% of students categorized as complete, exceeding the indicators of success with the achievement of class competencies reaching more than 75%.